Procrastination markets - Paul Heidhues; Takeshi Murooka; Botond Kőszegi (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
We develop models of markets with procrastinating consumers where competition operates - or is supposed to operate - both through the initial selection of providers and through the possibility of switching providers. As in other work, consumers fail to switch to better options after signing up with a firm, so at that stage they exert little downward pressure on the prices they pay. Unlike in other work, however, consumers are not keen on starting with the best available offer, so price competition fails at this stage as well. In fact, a competition paradox results: an increase in the number of firms or the intensity of marketing increases the frequency with which a consumer receives switching offers, so it facilitates procrastination and thereby potentially raises prices. By implication, continuous changes in marketing costs can, through a self-reinforcing process, lead to discontinuous changes in market outcomes. Sign-up deals do not serve their classically hypothesized role of returning ex-post profits to consumers, and in some cases even exacerbate the failure of price competition. Consumer procrastination thus emerges as a novel source of competition failure that applies in situations where other theories of competition failure do not.
Keywords: D11; D41; D43; D91; L11; L13; 330; Present bias; procrastination; price competition; competition failure; switching; subscription markets